Objective Selection Criteria between ALT and Radial Forearm Flap in Oral Soft Tissues Reconstruction - Elisa Benanti; Marta Starnoni; Antonio Spaggiari; Massimo Pinelli; Giorgio De Santis (Indian Journal of Plastic Surgery)
Different locoregional and free flaps were described for oral soft tissues reconstruction after oncological resections; however, free flaps remain the first choice. Among free flaps, the radial forearm flap (RFF) and the anterolateral thigh perforator flap (ALT) are preferred the most. The lack of standardization of the flap choice leaves the selection to the surgeon's experience. The purpose of our observational study is to provide an algorithm to support the flap choice for the reconstruction of oral soft tissues. Sixty patients with squamous cell carcinoma of oral soft tissues were enrolled in our study. All the patients underwent preoperative magnetic resonance imaging (MRI) to measure the three-dimensional size of the tumor. During the follow-up, the patients were evaluated by using the University of Washington-Quality of Life Questionnaire. The questionnaire score was better for small tumors and worse for large tumors in both functional and relational fields. We observed that most of the overlapping results were obtained for small defects and the choice of RFF, as well as for large defects and the use of ALT. We observed that in the preoperative time, it is possible to select which flap between radial forearm and ALT is more appropriate for oral soft tissues defects reconstruction, according to the size of the tumor evaluated by MRI. We propose a decisional algorithm that suggests the type of flap to use between ALT and RFF.